CLERGY SEXUAL MISCONDUCT: THROUGH THE LENS OF THE LOST SHEPHERDS - Espina, Ma. Leah Ann C. (Asian Horizons, 2020)
This qualitative research study deals with the experiences of priests who have committed sexual misconduct. Most studies on the reasons of clergy sexual abuse were based on archival data, specifically, statistical analyses of psychological test results, from treatment centres where priest-perpetrators were sent for rehabilitation. Due to the social stigma and fear of lawsuits, qualitative data are few and often come from accounts of the victim. Using Interpretative Phenomenological Analysis (IPA), the research explored the question: What are the reasons that led priests to be involved in sexual misconduct? Four themes emerged: a) Experience of loneliness, b) Unresolved issues in the past, c) Failure to maintain boundaries and, d) Lack of balance in the priestly life. This research probed the world of the priests as they shared their own experiences so that others could enter and understand the circumstances that led them to engage in abuse. Results of this study will be helpful in developing prevention strategies and appropriate rehabilitation programs on the issue of clergy sexual abuse.